IQTISODIY O‘SISH: MAMLAKATLAR RIVOJLANISHINING ASOSIY OMILLARI VA ULARNING TA’SIRI (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
This article analyzes the concept of economic growth and its measurements, in particular the expression of economic growth through gross domestic product (GDP). The differences in economic growth and development, their main factors and impacts are considered. Also, information is provided on the rates of economic growth and its impact on sustainable development on the example of countries.